Intermediate between Idiopathic Hypereosinophilia and Chronic Eosinophilic Leukemia: A Report of Two Hypereosinophilic Cases with Possible Novel Molecular Mutations. (1st September 2021) - Choudhuri, Jui; Eskandari, Mohammad; Shi, Yang; Wang, Yanhua
Abstract : To distinguish a reactive eosinophilia from its malignant counterpart is challenging. Establishing clonality of the eosinophils is crucial and considered the determining factor for establishing a diagnosis. Cases of hypereosinophilia without clear reactive etiologies, no evidence of end-organ damage, normal cytogenetics, and no molecular mutations are termed as "Idiopathic Hypereosinophilia (IHE)." For cases which lie between the spectrum of chronic eosinophilic leukemia (CEL) and IHE, identification of underlying molecular abnormalities might be helpful in better understanding the disease process and prognosis. Here, we report two cases of hypereosinophilia in which five possible novel molecular mutations were identified by targeted next-generation sequencing (NGS) analysis. They were FBXW7, KM2A, TCF3, ERBB4, and MET. With multiple genetic mutations, these cases could be classified as chronic eosinophilic leukemia. Both these young patients responded well to steroid therapy. While targeted NGS is a useful tool in identifying new molecular mutation associated with hypereosinophilia, our cases raise the question of further investigating this entity and if there is a possibility of an intermediate category lying between the spectrum of CEL and IHE. Defining hypereosinophilia with clonal molecular abnormality as a malignant process may need to be revisited. Even though attempts are being made to identify mutations in IHE, it might be more significant clinically to differentiate them based on response to steroid therapy and prognosis.